A Christian Ethical Dilemma: Is the Death Penalty for Drug Dealers a Solution? - Beis, Eka Herodian; Parapat, Christopher Dephelin; Sarumaha, Nikodemus; Mahendra, Sheza Chris (MAHABBAH: Journal of Religion and Education, 2024)
This study examines the Christian ethical dilemma surrounding the application of the death penalty for drug dealers in Indonesia. Although Law No. 35/2009 stipulates capital punishment for major narcotics crimes, drug abuse rates remain high, raising questions about its effectiveness. From a Christian ethical perspective, the issue is contentious—while the Old Testament supports retributive justice for grave offenses, the New Testament emphasizes love, forgiveness, and opportunities for repentance. Using a qualitative descriptive approach with normative-theological and legal frameworks, this research analyzes theological arguments, legal provisions, and moral implications of capital punishment in drug-related crimes. Findings reveal that while proponents view the death penalty as a deterrent and a means of protecting society, opponents argue it contradicts Christian values of grace and rehabilitation, risks irreversible injustice, and fails to address root causes. The study concludes that a rehabilitative and restorative justice approach, aligned with Christian principles of love and justice, offers a more holistic and humane alternative for addressing drug trafficking in Indonesia.